Health-related quality of life after otologic surgical treatment for chronic otitis media: systematic review - Schouwenaar, Esther M. M.; Hellingman, Catharine A.; Waterval, Jérôme J. (Frontiers in Neurology, 2023)
Objective This systematic review aims to describe the impact of otologic surgery as a treatment for chronic otitis media (COM) on the Health-Related Quality of Life (HRQoL) of adult patients. Methods A literature search was performed in PubMed, Scopus, Embase, and Web of Science until May 2023. Prospective studies including adult patients with COM (cholesteatoma) who underwent canal wall up mastoidectomy, canal wall down mastoidectomy, or tympanoplasty without mastoidectomy, with pre- and postoperative HRQoL measurements, were considered eligible. Questionnaire validation studies were excluded. The risk of bias and study quality were evaluated with a Quality Assessment Tool (for before-after studies with no control group). To assess the change in HRQoL, pre- and postoperative HRQoL values and absolute changes were extracted, synthesized, and presented in tables. Standardized mean differences (SMD) were calculated to enhance comparisons. Results Of the 720 studies identified, 16 met the inclusion criteria of this review. Different questionnaires were used throughout the studies. The CES and COMOT-15 were used in five studies and the ZCMEI-21 and COMQ-12 in three studies. All studies indicated statistically significant improvement in HRQoL from pre- to postoperative, measured with disease-specific HRQoL questionnaires. General HRQoL questionnaires did not show significant improvement. Calculated SMDs ranged from 0.24 to 6.99. Discussion and conclusion Included studies had low (n = 10) to high (n = 6) risk of bias and poor (n = 4), fair (n = 7) or good (n = 5) study quality. Surgical treatment positively impacts the HRQoL of adult COM patients with and without cholesteatoma. However, the clinical relevance of the reported changes is unknown due to the lack of minimal clinically important differences (MCID) or cut-off values in each questionnaire. Therefore, further research regarding the MCIDs of each questionnaire is needed. Future research should also report preoperative chief symptoms and indications for surgery to improve individual patient counseling.